EFFECTIVENESS OF SCHEMA THERAPY ON MALADAPTIVE SCHEMA MODES OF YOUNG ADULTS WITH BORDERLINE PERSONALITY FEATURES - Rimsha Tanveer Malik, Zainab Hussain Bhutto & Zainab F. Zadeh (Pakistan Journal of Psychology, 2021)
The present research aimed to investigate the effectiveness of schema therapy on maladaptive schema modes of young adults with borderline personality features. It included 17 female participants from Karachi who were screened for borderline personality features through Borderline Symptom List-95 (Bohus et al., 2005). Experimental group had 9 and wait-list control group had 8 participants. It was hypothesized that experimental group participants’ innate child modes (vulnerable, angry, impulsive) and dysfunctional parent modes (punitive, demanding) would differ significantly from wait-list control group after receiving 12 individual schema therapy sessions. To assess their modes, Schema Mode Inventory-1st Edition (Young et al., 2014) was administered at pretest and posttest. The results showed that experimental group’s maladaptive modes significantly reduced and differed from wait-list control group in post-test, except for punitive parent mode. Additional results and implications are also mentioned.